Effective Leadership Strategies: Bridging Gaps in the Latin American Educational System - Rodriguez-Barboza, Jhonny Richard; Bartra-Rivero, Karina Raquel; Pablo-Huamani, Rebeca; Sandoval-Lara, Elizabeth; Ramos-Ventura, Carmen Gisela (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
This research addresses School Leadership (LDE) in Latin American educational institutions, focusing on how leadership affects educational quality and school climate. A descriptive bibliographic review methodology was employed, analyzing 38 indexed journal articles to identify trends and patterns in school leadership. The results revealed a recurring concern about the lack of managerial skills and the need for continuous training for managers, teachers, and administrative staff. Additionally, the importance of adapting leadership styles to promote positive learning environments and active participation of all members of the educational community was highlighted. The conclusions underscore the need for innovative strategies to improve management skills and promote an inclusive and enriching school climate. The discussion highlights the variability in the effectiveness of current leadership practices and the need for more detailed research approaches to better understand the impact of LDE in the educational field, suggesting that effective leadership is key to facing challenges and improving the quality of education.